Development Results in Middle-Income Countries : An Evaluation of the World Bank's Support - Independent Evaluation Group (Washington, DC: World Bank, 2012)
This IEG evaluation brings a fresh perspective to the debate by assessing the development effectiveness of the Bank's recent work. It presents evidence -- including views from the client countries themselves -- about the outcomes of the Bank's support to individual countries over the past 12 years. It also spotlights three growing dimensions of the Bank Group's role -- sharing knowledge across countries, engaging countries in global programs, and combining support to the public and private sectors